2015
DOI: 10.1111/jam.12906
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and chemometric modelling of South African propolis

Abstract: Based on the good antimicrobial activity observed for SA propolis, this natural resource shows promise and should be considered for development which may contribute to growing the bio-economy in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 57 publications
5
36
0
2
Order By: Relevance
“…Interesting results were also published by Suleman and colleagues [51]. Some of 39 South Africa propolis samples exhibited much higher antistaphylococcal activity in comparison to three tested samples of Brazilian propolis with MIC and MBC values of only 6 μg/mL [51]. Al-Waili and coworkers revealed that ethanolic extracts of propolis collected from Saudi Arabia (EEPS) and from Egypt (EEPE) efectively inhibited the growth of antibiotic resistant E. coli, S. aureus and C. albicans in single and polymicrobial cultures [52].…”
Section: Bee Products and Essential Oils As Alternative Agents For Trsupporting
confidence: 59%
See 1 more Smart Citation
“…Interesting results were also published by Suleman and colleagues [51]. Some of 39 South Africa propolis samples exhibited much higher antistaphylococcal activity in comparison to three tested samples of Brazilian propolis with MIC and MBC values of only 6 μg/mL [51]. Al-Waili and coworkers revealed that ethanolic extracts of propolis collected from Saudi Arabia (EEPS) and from Egypt (EEPE) efectively inhibited the growth of antibiotic resistant E. coli, S. aureus and C. albicans in single and polymicrobial cultures [52].…”
Section: Bee Products and Essential Oils As Alternative Agents For Trsupporting
confidence: 59%
“…The authors noticed that in milk the bactericidal dose was at least 20-fold greater [50]. Interesting results were also published by Suleman and colleagues [51]. Some of 39 South Africa propolis samples exhibited much higher antistaphylococcal activity in comparison to three tested samples of Brazilian propolis with MIC and MBC values of only 6 μg/mL [51].…”
Section: Bee Products and Essential Oils As Alternative Agents For Trsupporting
confidence: 54%
“…In a search for new antimicrobials Suleman, van Vuuren, Sandasi, and Viljoen () examined extracts from propolis, a sticky resin found in beehives, by LC‐MS, chemical analyses, and bioassays. The data were evaluated using multivariate data analysis by orthogonal projections to latent structures (OPLS) and an S‐plot function.…”
Section: Chemometrics In Food‐related Disciplinesmentioning
confidence: 99%
“…Nevertheless, research on propolis in sub-Saharan Africa has shown that, in general, African propolis -like the propolis found in other tropical regions -is rich in terpenoids, including α-amyrine, β-amyrin, α-amyryl acetates, β-amyryl acetates, n-alkanes, n-alkenes, methyl n-alkanoates, and long-chain wax esters, among other compounds. [25][26][27][28][29][30] The price of propolis varies according to its source and quality. For example, Chinese propolis is offered for sale at about €25 to €50 euros per kg, while the Brazilian propolis is offered at higher prices (€100 to €150 euros per kg).…”
Section: Introductionmentioning
confidence: 99%